PENERAPAN METODE PEMBELAJARAN GAME BASED LEARNING BERBANTUAN MEDIA WORDWALL DALAM MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS VI - Nur Azhar, Muthia; Nurmahanani, Indah; Sholihah Rosmana, Primanitas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
One aspect of language skills in elementary school is reading ability. Reading ability is needed to understand information or reading content, this is called reading comprehension ability. Classroom action research was carried out to overcome the lack of reading comprehension skills experienced by class VI students. A lack of reading comprehension skills can be seen in students who are confused in understanding the reading text. The researcher used the classroom action research method by applying the Game-Based Learning method assisted by Wordwall media in improving the reading comprehension skills of class VI students. The subjects studied by the researchers were class VI students at SDN 2 Batutumpang with a total of 40 people. The instruments used were activity observation sheets and reading comprehension tests. The results of the research show an increase in activity observations and reading comprehension ability tests in cycle 1 to cycle 2. The results of students' reading comprehension ability in cycle 1 were 30% then increased in cycle 2 by 90%. It can be concluded that the application of the Game-Based Learning method assisted by Wordwall media can improve the reading comprehension ability of class VI students. Keywords: game based learning, wordwall media, reading comprehension